Climate Impacts and Potential Drivers of the Unprecedented Antarctic Ozone Holes of 2020 and 2021. Issue 10 (24th May 2022) - Yook, Simchan; Thompson, David W. J.; Solomon, Susan
Abstract: The latter months of 2020 and 2021 were marked by two of the largest Antarctic ozone holes on record. That such large ozone holes occurred despite ongoing ozone recovery raises questions about their origins and climate impacts. Here we provide novel evidence that supports the hypothesis that the ozone holes were influenced by two distinct and extraordinary events: the Australian wildfires of early 2020 and the eruption of La Soufriere in 2021. We further reveal that both ozone holes were associated with widespread changes in Southern Hemisphere climate that are consistent with the established climate impacts of Antarctic ozone depletion, including a strengthening of the polar stratospheric vortex, enhanced surface westerlies over the Southern Ocean, and surface temperature changes over Antarctica and Australia. The results thus provide suggestive evidence that injections of both wildfire smoke and volcanic emissions into the stratosphere can lead to hemispheric‐scale changes in surface climate. Plain Language Summary: The Antarctic ozone hole is characterized by dramatic decreases in stratospheric ozone during the austral spring months. The ozone hole is expected to recover over the next few decades in response to the phasing out of ozone‐depleting substances. However, the latter months of 2020 and 2021 were marked by two of the largest Antarctic ozone holes on record, which raises questions about their origins and climate impacts. Here we provide novel evidence that supports the hypothesis that the ozone holes were influenced by two extraordinary events: the Australian wildfires of early 2020 and the eruption of La Soufriere in 2021. We further reveal that both ozone holes were associated with changes in Southern Hemisphere surface climate consistent with the established climate impacts of Antarctic ozone depletion. Together, the results provide suggestive evidence that injections of both wildfire smoke and volcanic emissions into the stratosphere can lead to hemispheric‐scale changes in surface climate. Key Points: The large Antarctic ozone holes of 2020 and 2021 were accompanied by stratospheric burdens of wildfire and volcanic emissions, respectively Both ozone holes were associated with pronounced changes in surface climate consistent with the impacts of Antarctic ozone depletion Together, the linkages suggest that both wildfire smoke and volcanic emissions can lead to large‐scale changes in surface climate